2017
DOI: 10.1177/1471301217723772
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to nature gardens has time-dependent associations with mood improvements for people with mid- and late-stage dementia: Innovative practice

Abstract: Exposure to green space and nature has a potential role to play in the care of people with dementia, with possible benefits including improved mood and slower disease progression. In this observational study at a dementia care facility in the UK, we used carer-assessed measures to evaluate change in mood of residents with mid- to late-stage dementia following exposure to a nature garden. We found that exposure to nature was associated with a beneficial change in patient mood. There was a non-linear relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 7 publications
0
48
0
Order By: Relevance
“…Two spatially varying measures related to long-term impacts of the built environment ( Figure 2), which may in uence the prevalence of dementia (de Keijzer et al, 2016;White et al, 2018;Wu et al, 2015), were used in this study: 1) urban compactness, and 2) greenness.…”
Section: Measures Of Long-term Environmental Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two spatially varying measures related to long-term impacts of the built environment ( Figure 2), which may in uence the prevalence of dementia (de Keijzer et al, 2016;White et al, 2018;Wu et al, 2015), were used in this study: 1) urban compactness, and 2) greenness.…”
Section: Measures Of Long-term Environmental Impactsmentioning
confidence: 99%
“…In addition, human behaviors, activities of daily living and spatial mobility of older adults could also be affected by the environment surrounding their residences (Cerin et al, 2013); therefore, this has also led to a research trend of investigating in uences of built and social environments on the prevalence of dementia (Wu et al, 2015). For example, recent studies have found that green space as a built environmental factor reduces dementia and its associated diseases (de Keijzer et al, 2016;White et al, 2018;Wu et al, 2015). Some studies have also documented the adverse impacts of socioeconomic and racial problems on these diseases (Cadar et al, 2018;Chiao et al, 2014;Cook, 2019;Van De Vorst et al, 2016;Yaffe et al, 2013), and other studies have found that long-term air pollution (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of moderate to severe dementia patients, exposure to nature via carer-mediated exposure to a nature-rich garden was found to result in a beneficial change in patient mood [37]. Interestingly, improvements were nonlinear and associated with shorter exposure periods, with no additional improvements with exposure beyond 80-90 min [37].…”
Section: Multisensory Environments (Mses)mentioning
confidence: 99%
“…In two separate studies, Goto et al found that viewing a Japanese garden twice a week for 15 sessions over 8 weeks reduced heart rate, evoked short-term and long-term memories and improved behavioural symptoms in nursing home residents with dementia in the USA and in hospitalized dementia patients in Japan [35,36]. In a study of moderate to severe dementia patients, exposure to nature via carer-mediated exposure to a nature-rich garden was found to result in a beneficial change in patient mood [37]. Interestingly, improvements were nonlinear and associated with shorter exposure periods, with no additional improvements with exposure beyond 80-90 min [37].…”
Section: Multisensory Environments (Mses)mentioning
confidence: 99%
“…There are no previous controlled trials of nature gardens in the general adult population or in clinical populations. However, White et al 9 have recently shown that time spent outdoors in a purposely renovated garden, with active and passive spaces and a rich sensory environment that included fruit trees and vegetable beds, was positively associated with improvements in mood in residential dementia patients. Furthermore, this study showed that this association was time dependent, with improvements in mood occurring after just 20 min and peaking at a duration of 80–90 min, suggesting there is both a minimal and a maximal time to be spent outdoors in nature to accrue health benefits.…”
Section: Findings From Previous Researchmentioning
confidence: 99%